Corrosion of Mortar Mixed With Quarry Dust as Fine Aggregate Due to Sulfuric Acid - Khamput, Prachoom (Frontiers in Engineering Innovation Research, 2006)
This research studies the corrosion on quarry dust mortars due to sulfuric acid. By fully using quarry dust instead of sand and w/c = 0.45, the mortar specimens are formed and cured for 28 days before immerse them into 5 % (W/W) of sulfuric acid solution. From the results, it is found that quarry dust mortars can resist the corrosion better than normal mortar.